Ratiometric Electrochemical Biosensor Based on Internally Controlled Duplex PCR for Detection of Mycobacterium Tuberculosis. Issue 2 (7th February 2022) - Bunyarataphan, Sasinee; Prammananan, Therdsak; Japrung, Deanpen
Abstract : The pathogenic bacteria Mycobacterium tuberculosis (MTB) is responsible for tuberculosis which is well known for the globally leading cause of death. The likelihood of false negative interpretation as well as potential influence from intrinsic and extrinsic factors are considerably minimized by the incorporation of internal control (IC) detection into the developed assay platform. Ratiometric electrochemical biosensor (REC biosensor) for detection of MTB was developed based on the IC integration via duplex PCR (dPCR) and a dual-signal electrochemical readout. The MTB- or IC-specific PNA probe was labeled with methylene blue (MB) or ferrocene (FC), respectively at the C terminus, producing a strong square wave voltammetry (SWV) signal. Interaction of the ICdPCR product could induce changes in the dynamics of these two redox-labeled PNA probes (MTB-MB and IC-FC) that were attached to the screen-printed gold electrode (SPGE) via formation of a self-assembled monolayer. Using this MB as a reporter and FC as an IC, the REC ICdPCR biosensor achieved a broad detection range from 10 fM to 10 nM and a detection limit of 1.26 fM, corresponding to approximately 2.5 bacteria cells. The REC ICdPCR biosensor was applied to MTB measurement in practical samples, exhibiting high accuracy and more importantly high practicability.